The Mollusca. - Trueman, E. R. (Edwin Royden), 1922-; Clarke, Malcolm R. (Mollusca, 1985)
FROM THE GENERAL PREFACE: This multivolume work, The Mollusca, had its origins in the mid 1960s with the publication of two volumes entitled Physiology of Mollusca and edited by Wilbur and Yonge. In those volumes, 27 authors collaborated to summarize the status of the conventional topics of physiology as well as biochemistry, reproduction and development, and ecology. Within the past two decades, there has been a remarkable burgeoning of molluscan research generally and with it the development of new fields of investigation. During the same period, several excellent books on molluscs have appe.